68Ga-DOTA-NT-20.3 Neurotensin Receptor 1 PET Imaging as a Surrogate for Neuroendocrine Differentiation of Prostate Cancer - Wu, Wenyu; Yu, Fei; Zhang, Pengjun; Bu, Ting; Fu, Jingjing; Ai, Shuyue; You, Qinqin; Shi, Liang; Shao, Guoqiang; Wang, Feng; Hodolic, Marina; Guo, Hongqian (Journal of nuclear medicine, 2022)
Prostate-specific membrane antigen (PSMA)-negative neuroendocrine prostate cancer (PCa) is a subtype of PCa likely to be lethal, with limited clinical diagnostic and therapeutic options. High expression of neurotensin receptor subtype 1 (NTR1) is associated with neuroendocrine differentiation of PCa, which makes NTR1 a potential target for neuroendocrine PCa. In this study, the NTR1-targeted tracer 68Ga-DOTA-NT-20.3 was synthesized, and its affinity to androgen-dependent (LNCap) and androgen-independent (PC3) xenografts was determined. Methods: 68Ga-DOTA-NT-20.3 was labeled using an automated synthesizer module, and its stability, labeling yield, and radiochemical purity were analyzed by radio-high-performance liquid chromatography. Receptor binding affinity was evaluated in NTR1-positive PC3 cells by a competitive binding assay. The biodistribution of 68Ga-DOTA-NT-20.3 in vivo was evaluated in PC3 and LNCap xenografts by small-animal PET imaging. NTR1 expression was identified by immunohistochemistry and immunofluorescence evaluation. Results: 68Ga-DOTA-NT-20.3 was synthesized successfully, with a yield of 88.07% ± 1.26%, radiochemical purity of at least 99%, and favorable stability. The NTR1 affinity (half-maximal inhibitory concentration) for 68Ga-DOTA-NT-20.3 was 7.59 ± 0.41 nM. Small-animal PET/CT of PC3 xenograft animals showed high-contrast images with intense tumor uptake, which revealed specific NTR1 expression. The tumors showed significant radioactivity (4.95 ± 0.67 percentage injected dose per gram of tissue [%ID/g]) at 1 h, which fell to 1.95 ± 0.17 %ID/g (P < 0.01, t = 8.72) after specific blockage by neurotensin. LNCap xenografts had no significant accumulation (0.81 ± 0.06 %ID/g) of 68Ga-DOTA-NT-20.3 at 1 h. In contrast, 68Ga-PSMA-11 was concentrated mainly in LNCap xenografts (8.60 ± 2.11 %ID/g), with no significant uptake in PC3 tumors (0.53 ± 0.05 %ID/g), consistent with the in vitro immunohistochemistry findings. Biodistribution evaluation showed rapid clearance from the blood and main organs (brain, heart, lung, liver, muscle, and bone), with significantly high tumor-to-liver (4.41 ± 0.73) and tumor-to-muscle (12.34 ± 1.32) ratios at 60 min after injection. Conclusion: 68Ga-DOTA-NT-20.3 can be efficiently prepared with a high yield and high radiochemical purity. Its favorable biodistribution and prominent NTR1 affinity make 68Ga-DOTA-NT-20.3 a potential radiopharmaceutical for the detection of PSMA-negative PCa and identification of neuroendocrine differentiation.
Keywords: Prostatic Neoplasms; neuroendocrine differentiation; Gallium Isotopes; nádory prostaty; Receptors, Neurotensin; Humans; androgeny; izotopy gallia; 68Ga-DOTA-NT-20.3; Androgens; tkáňová distribuce; heterocyklické sloučeniny monocyklické; receptory neurotensinu; lidé; zvířata; prostate cancer; neurotensin receptor subtype 1; Tissue Distribution; Male; Positron Emission Tomography Computed Tomography; Heterocyclic Compounds, 1-Ring; nádorové buněčné linie; Positron-Emission Tomography; neurotensin; PET; radioizotopy galia; Animals; Cell Line, Tumor; Gallium Radioisotopes; mužské pohlaví; radiofarmaka; pozitronová emisní tomografie; PET/CT; Neurotensin; Radiopharmaceuticals